INCREASING STUDENTS’ VOCABULARY MASTERY BY USING FLASHCARDS AT SMP NEGERI 2 ESSANG - Regina Siso; Paula Rombepajung; Javier Tuerah (SoCul: International Journal of Research in Social Cultural Issues, 2022)
During the COVID-19 pandemic, education has become an important issue especially how distance learning is one of the options taken by almost all schools in Indonesia in reducing the spread of the COVID-19 virus. In this connection, it is related with the conditions where English is no longer the main subject in elementary school and will greatly affect the learning process of students when they enter junior high school where they will learn a lot of basic things from English and actually taught during elementary school. This research is proved whether the use of Flashcards in teaching vocabulary can increase students’ vocabulary mastery or not. This research delimits on verb only, especially to the common words or daily words used in describing the action, for instance: ordinary verb, transitive verb and intransitive verb. The verb, which is needed, and do not need the object and also the primary verb in used. The findings show that the post-test had a higher score than the pre-test. Pre-test shown the Mean score (T ̅1 = 73.63) and Standard Deviation (S12 = 76.6) are the lower than post-test in which the mean score (T ̅2 = 87.5) and Standard Deviation (S22 = 87.5) in post-test. It meant that the result of post-test after treatment is better than the pre-test before treatment. Based on the result of research, appyling technique using Flashcards to increasing students’ vocabulary mastery is effective.